Penggunaan Tata Bahasa Netizen Dikolom Komentar Instragram Yang Membicarakan Tentang Pemilu 2024 - Siti Aisyah; Ferdy Briliant Oktaviano; Nensy Megawati Simanjuntak (Lembag, 2024)
Abstract This study aims to investigate the use of netizen grammar in the Instagram comment section discussing the 2024 Election issue, with a focus on language style, conversational patterns, and their impact on public opinion and the democratic process. Employing a qualitative approach, data for this research were collected through direct observation of netizen comments on Instagram. When netizens engage in communication about political issues like the 2024 Election, the grammar they use plays a crucial role in shaping how messages are conveyed and received. This study highlights several common grammar mistakes that may occur, such as spelling errors, improper punctuation usage, and the use of impolite language. For instance, the use of